2020
DOI: 10.1002/eng2.12121
|View full text |Cite
|
Sign up to set email alerts
|

Fiber optic deployment challenges and their management in a developing country: A tutorial and case study in Ghana

Abstract: The telecommunication industry in Ghana has undergone various stages of transformation. The industry has experienced exponential growth over the last decades. Sustaining this growth hinges on efficient infrastructural deployment and management. Fiber optics technology has become the primary network infrastructure and a communication medium, which provides higher bandwidth capacity high speed for current and emerging technologies. As the demand for new technology and services increases, fiber optics technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…The values obtained for the evaluation matrix MSE and MAE were 0.061291 and 0.080143, respectively, indicating the predictive model is good for the prediction of the exact distance of faults in underground fiber cable cut. Identifying and repairing the fault in the underground optical networks significantly reduce the cost of repairing the faults 41 and then overcome the challenges identified by Reference 42.…”
Section: Resultsmentioning
confidence: 99%
“…The values obtained for the evaluation matrix MSE and MAE were 0.061291 and 0.080143, respectively, indicating the predictive model is good for the prediction of the exact distance of faults in underground fiber cable cut. Identifying and repairing the fault in the underground optical networks significantly reduce the cost of repairing the faults 41 and then overcome the challenges identified by Reference 42.…”
Section: Resultsmentioning
confidence: 99%
“…The cuts of underground fiber cables reduce the optical network availability, affect customer experience, and increases the MNOs cable repair costs. The rampant underground cable cut further reduces rural network expansion and affects last mile connectivity strategies [1][2][3].…”
Section: Hard Failures In Underground Optical Networkmentioning
confidence: 99%
“…have experienced similar hard failures in the underground optical networks. Studies have found that underground fiber cables were more likely to be cut in rural areas, even though several unapproved activities in urban areas have accounted to a higher number of fiber optic cables destructions in a given area [1,3].…”
Section: Hard Failures In Underground Optical Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…In NT, civil department coordinates the design and implementation of civil related works. The major challenges for this type of work is to establish coordination with the related other offices such as road department, urban development department, electricity authority, and other related departments(Nyarko-Boateng et al, 2020).…”
mentioning
confidence: 99%